2011
DOI: 10.1017/s1742170511000378
|View full text |Cite
|
Sign up to set email alerts
|

Water infiltration and surface-soil structural properties as influenced by animal traffic in the Southern Piedmont USA

Abstract: Surface-soil structural condition in perennial pastures is expected to be modified by how forage is (a) harvested through haying or grazing and (b) stimulated through source of nutrients applied, as well as by compactive forces, e.g., grazing cattle or hay harvest machinery. Changes in surface-soil condition can affect hydrologic processes that have important implications for plant growth, greenhouse gas emissions and off-site water quality. We determined the effects of harvest management and nutrient source o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 32 publications
(43 reference statements)
0
14
1
1
Order By: Relevance
“…This fact leads to a greater release of root exudates, which associated with the addition of residues (urine + feces) promotes a greater macropore distribution, as observed by Souza et al (2010a). These changes improve the soil structure, leading to greater infiltration, aeration, and water storage (Franzluebbers et al, 2011).…”
Section: Resultsmentioning
confidence: 94%
“…This fact leads to a greater release of root exudates, which associated with the addition of residues (urine + feces) promotes a greater macropore distribution, as observed by Souza et al (2010a). These changes improve the soil structure, leading to greater infiltration, aeration, and water storage (Franzluebbers et al, 2011).…”
Section: Resultsmentioning
confidence: 94%
“…For example, Masri and Ryan 72 found infiltration rates increased when a diverse annual crop rotation included livestock as compared to when the systems included crops only. Franzluebbers et al 73 reported increased infiltration rates in pasture-based systems with versus without livestock, but only when a lower grazing intensity was utilized. It is also important to note that cropland grazing typically represents only one component of a diversified farming system that may have different outcomes when assessed on a larger scale.…”
Section: Discussionmentioning
confidence: 99%
“…While ultimately, soil type and water delivery rate are the overarching determinants of infiltration rate, livestock, and pasture management practices can alter this process (Laycock and Conrad, 1967;Savory and Butterworth, 1999;Franzluebbers et al, 2012). However, comparisons between the effects of livestock management practices on water infiltration and soil compaction (i.e., bulk density) are inconsistent.…”
Section: Impacts To Water and Soil-water Interactions Water Pollutionmentioning
confidence: 99%